2009
DOI: 10.1292/jvms.71.577
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Canine Protease-Activated Receptor-2 and its Expression in Normal Dog Tissues and Atopic Skin Lesions

Abstract: ABSTRACT. Protease-activated receptor-2 (PAR-2) belongs to a new G protein-coupled receptor subfamily and is activated by serine proteases. PAR-2 has been demonstrated to play an important role in inflammation and immune response in allergic diseases. In this study, we cloned canine PAR-2 cDNA from the canine kidney by RT-PCR. The canine PAR-2 clone contained a full-length open reading frame encoding 397 amino acids that had 84% and 80% homology with human and mouse homologues, respectively. Canine PAR-2 mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…The proteases from allergens are associated with various homeostatic responses in skin disease, such as inflammation, immune responses, host defense, chemotaxis, cytokine expression, vascular function, tissue repair and apoptosis . Serine proteases, such as trypsin or mast cell tryptase, can activate PAR‐2 signals . The present AD model, which was developed by HDM sensitization, could present some unique changes of the homeostatic responses.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The proteases from allergens are associated with various homeostatic responses in skin disease, such as inflammation, immune responses, host defense, chemotaxis, cytokine expression, vascular function, tissue repair and apoptosis . Serine proteases, such as trypsin or mast cell tryptase, can activate PAR‐2 signals . The present AD model, which was developed by HDM sensitization, could present some unique changes of the homeostatic responses.…”
Section: Discussioncontrasting
confidence: 87%
“…In the present study, however, the intensity of PAR‐2 and TSLP in immunofluorescence was not significantly increased in atopic dogs compared with normal animals. Another study also reported that the mRNA level of PAR‐2 was not significantly different between atopic dogs (lesional skin) and normal animals; it concluded that the level of PAR‐2 mRNA transcription may not be associated with development of canine AD …”
Section: Discussionmentioning
confidence: 88%
“…PARs belong to a subfamily of G protein‐coupled, 7‐transmembrane domain receptors, activated by specific proteolytic cleavage of their extracellular amino termini by proteases . Among PAR‐1 to ‐5, PAR‐2 has been shown to be expressed in the keratinocytes of humans, mice and dogs . Recent studies in humans and dogs have indicated that activation of TLRs and PAR‐2 in keratinocytes induces the production of cytokines and chemokines necessary for initiating and maintaining allergic inflammation.…”
Section: Cutaneous Immune Reactionsmentioning
confidence: 99%
“…36,37 Among PAR-1 to -5, PAR-2 has been shown to be expressed in the keratinocytes of humans, 38 mice 39 and dogs. 40,41 Recent studies in humans and dogs have indicated that activation of TLRs and PAR-2 in keratinocytes induces the production of cytokines and chemokines necessary for initiating and maintaining allergic inflammation.…”
Section: Cutaneous Immune Reactionsmentioning
confidence: 99%
“…These findings suggest that the interactions between PAR-2 and luminal serine proteases may be associated with the pathogenesis of IBD. As in humans and rodents, PAR-2 is prominently expressed in the small intestine and colon in dogs [27], which indicates that PAR-2 may also play a role in gut inflammation in this species. However, little is known about the pathophysiological roles of PAR-2 and luminal serine proteases in canine IBD.…”
mentioning
confidence: 99%